Female Agency and Scandal: Doña Josefa de Angulo in 17th-Century Mexico City - Curcio-Nagy, Linda A. (Anuario de Historia de América Latina, 2025)
This essay examines the life of Doña Josefa de Angulo through the lens of a 1661 Inquisition case. Josefa, whose much older husband, Juan de Vilches, deposited her at the Recogimiento de la Magdalena (the home for wayward women) in Mexico City, demonstrated a concerted effort to live life on her terms, ignoring the expectations for a married woman of some socio-economic standing. She dramatically altered life at the recogimiento and set in motion a series of scandalous events that involved employees at that institution, the archbishop and his staff, her stepchildren, the inquisitors, and her confessor Miguel de Palmares, who she accused of solicitation in the confessional. She challenged normative ideas about marriage, obedience to male authority, female agency, and the very purpose of the recogimiento. Her story illuminates the complicated relationship between gendered social control and the nature of scandal in colonial Mexico City.